Body Scrub Salt Formulation from Cinnamomum burmannii (C. Ness & T. Ness) Blume Extract as an Antibacterial Against Staphylococcus aereus - Surbakti, Chemayanti; Nobelia, Christine Ruth; Hanum, T. Ismanelly (Indonesian Journal of Pharmaceutical and Clinical Research, 2024)
Skincare is currently a major focus in the beauty industry with skin exfoliation being an important step. One product used to exfoliate the skin is a body scrub, which contains ingredients such as himalayan salt and cinnamon bark extract. Himalayan salt helps remove dead skin cells and moisturizes the skin, while cinnamon extract has antimicrobial properties that can protect the skin from bacteria. This study aims to formulate and test the effectiveness of body scrub with skin analyzer and antibacterial activity against Staphylococcus aureus. This research uses an experimental method with several stages, namely plant material collection, plant identification, powder making, extract making, preparation making, evaluation and stability, effectiveness test with skin analyzer and antibacterial activity against Staphylococcus aureus. The 10% body scrub has better effectiveness than 0%; 2.5% and 5% which obtained a percent increase in skin moisture (71.62%), a decrease in the number of blemishes on the skin (70.73%) and a decrease in pore size on the skin (76.38%) for 4 weeks of treatment. In testing antibacterial activity, the 10% concentration was also considered the optimal concentration because it had the greatest inhibition of 14.20 Â± 0.59 mm. The results concluded that Himalayan salt and cinnamon bark extract can be formulated into a body scrub dosage form that meets the stability requirements and has the effectiveness in moisturizing, smoothing, and brightening the skin. The formula that has the most effective antibacterial activity is a body scrub containing extracts with a concentration of 10% against Staphylococcus aureus bacteria.